(untitled) (Archive of Conferences, 2021)
Language, as a system, is in constant motion and development. This is his comes from the social nature: language and society, language and consciousness, between language and thought two-way communication determines their impact on each other - in society socio-political processes, scientific and technological development, economic and Reforms in the field of education include new words and terms in the vocabulary of the language. occurrence, obsolescence of currently known words and lexemes, to the historical category requires rotation. This process of lexemes in the vocabulary of the language obsolescence, resulting in lexical items such as historical words, archaisms and neologisms units.